2019
DOI: 10.1152/jn.00814.2018
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements do not play an important role in the adaptation of hand tracking to a visuomotor rotation

Abstract: Gouirand N, Mathew J, Brenner E, Danion FR. Eye movements do not play an important role in the adaptation of hand tracking to a visuomotor rotation. Adapting hand movements to changes in our body or the environment is essential for skilled motor behavior. Although eye movements are known to assist hand movement control, how eye movements might contribute to the adaptation of hand movements remains largely unexplored. To determine to what extent eye movements contribute to visuomotor adaptation of hand tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 54 publications
1
20
1
Order By: Relevance
“…Overall, those observations suggest that participants employed a rather robust gaze strategy that consists of positioning gaze between cursor and target but closer to the target. Although similar findings were observed when participants perform this tracking task with a joystick and a rotated cursor (Gouirand et al, 2019), the current study demonstrates that this strategy (gaze on target first) holds for more complex mappings and full arm movements.…”
Section: Gaze Behavior Is Virtually Unaffected By Handcursor Dynamicssupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, those observations suggest that participants employed a rather robust gaze strategy that consists of positioning gaze between cursor and target but closer to the target. Although similar findings were observed when participants perform this tracking task with a joystick and a rotated cursor (Gouirand et al, 2019), the current study demonstrates that this strategy (gaze on target first) holds for more complex mappings and full arm movements.…”
Section: Gaze Behavior Is Virtually Unaffected By Handcursor Dynamicssupporting
confidence: 83%
“…When people perform full arm movements under a simple (one-to-one) hand-cursor relationship, their gaze is much closer to the target than the cursor (Danion & Flanagan, 2018), suggesting that an estimate of cursor position is accessible through peripheral vision and/or arm (efferent/afferent) signals. We recently showed that when participants track a moving target with a joystick, their gaze is also closer to the target than the cursor after adapting to a visuomotor rotation that rotates the cursor away from the hand but preserves a one-to-one mapping between cursor speed and hand speed (Gouirand et al, 2019). The goal of the current study was to determine whether fixating the target with the eyes is a gaze strategy that extends to full arm movements performed under more complex (nonlinear) hand-cursor mappings.…”
Section: Introductionmentioning
confidence: 99%
“…However, these analyses revealed no key difference between male and female participants. Although no explicit instruction was given regarding eye movements, as expected gaze was mainly directed to target motion 20,29 . Examining how close the gaze was from the target revealed no obvious sex differences.…”
Section: Similar Gaze Behavior In Male and Femalementioning
confidence: 94%
“…Although there is a clear consensus for a male advantage in throwing [13][14][15] , some evidence for a male advantage in visuomotor tracking have been reported [16][17][18][19] but they remain scarce and speak for further confirmation. Our primary objective was therefore to explore the robustness of sex difference in visuomotor tracking by taking advantage of a large dataset that was previously collected in our lab [20][21][22] . More important, we aimed at seeking for the mechanism underlying sex differences.…”
Section: Sex Differences In Visuomotor Tracking James Mathew 123 mentioning
confidence: 99%
“…In that case, the hand movements toward moving targets were adjusted to the delay in the trial in question, despite the delays being interleaved so that participants could not adapt to them. When participants look at a moving target while moving a delayed cursor toward it (Cámara et al, 2018) or while trying to track it with a cursor (Gouirand, Mathew, Brenner, & Danion, 2019), they must be using peripheral vision to guide the ongoing movement of the hand.…”
Section: Introductionmentioning
confidence: 99%